Exequatur on incapacity and deprivation of rights in electoral matters. A study from the perspective of PIL and Comparative Law, in the light of the judgement of the Supreme Court of Chile in case no. 87.878-2023 - Sánchez Cano, María Jesús; Santillán Santa Cruz, Romina (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper focuses on the study of an exequatur on incapacity and deprivation of rights in electoral matters. In particular, it analyses a judgement of the Supreme Court of Chile, issued in Rol Nº 87.878-2023, which recognises and executes a Spanish judgement, prior to the entry into force of Law 8/2021, which declared the total incapacity of a person and decreed the deprivation of his or her right to vote. Given the interest aroused by the aforementioned Chilean judgement, both from the perspective of Private International Law and Comparative Civil Law, the international and material elements that link the Spanish and Chilean legal systems in this case are confronted. To this end, beforehand, and in relation to the matter of interest here, some provisions of the Convention on the Rights of Persons with Disabilities, the Hague Convention of 13 January 2000 on the International Protection of Adults, the Law on International Legal Cooperation in Civil Matters, Organic Law 2/2018 and Law 8/2021 are dealt with.
Keywords: Exequatur; voting right; legal capacity; incapacity; international protection of adults; International Private Law